Upaya Guru Pendidikan Agama Islam (PAI) dalam Membina Akhlak terhadap Sesama Siswa di SD Negeri 02 Pasaman - Lubis, Muhammad Rifki Abrori; Murniyetti, Murniyetti (ANWARUL, 2023)
This research is motivated by the lack of moral education provided by teachers in the educational unit, especially at Elementary Schools (SD). In shaping a child's moral character, referring to this background issue, the researcher was interested in conducting a more in-depth study on the Efforts of Islamic Religious Education (PAI) Teachers in Cultivating Morality Among Fellow Students at SD Negeri 02 Pasaman. This research aims to uncover the efforts of Islamic Religious Education (PAI) teachers in cultivating morality among fellow students, the obstacles faced by PAI teachers, and the efforts made by PAI teachers to overcome obstacles in fostering moral character among fellow students. Therefore, in conducting the research, the researcher chose the Field Research method. Hence, the appropriate method to use is qualitative. The data sources for this research consist of primary data, namely PAI teachers in SDN 02 Pasaman. While secondary data includes the curriculum, school archives, photographic documentation, and observation notes. The results of the research show that the efforts of Islamic Religious Education (PAI) teachers in cultivating morality among fellow students at SD Negeri 02 Pasaman are carried out through positive actions in their daily routines, such as setting a good example, spontaneous actions, and habituation in routine activities by PAI teachers at SD Negeri 02 Pasaman. This integration occurs in special programs involving weekly, monthly, and annual activities and is integrated into the learning process.